A crevice corrosion electrochemical testing device and its application

By designing a crevice corrosion electrochemical test device, using technical means such as three-electrode two-loop system and porous ceramic plugs, the problem of difficulty in detecting and evaluating crevice corrosion in the existing technology is solved, real-time monitoring of crevice corrosion and electrochemical parameters are achieved. Detailed testing revealed the mechanism of crevice corrosion and evaluated the crevice corrosion performance between different metal materials.

CN115452696BActive Publication Date: 2025-02-25INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110638935.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-08
Publication Date
2025-02-25
Estimated Expiration
2041-06-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect and evaluate the process and mechanism of crevice corrosion, especially the crevice corrosion performance between different metal materials.

Method used

A gap corrosion electrochemical testing device is designed. By designing a three-electrode and two-loop system in the gap, the device can monitor the electrochemical signals during gap corrosion and test the electrochemical parameters of the samples inside and outside the gap respectively. The device also uses porous ceramic plugs and PTFE mold to control the gap width and depth, allowing the monitoring of gap corrosion electrochemical signals between different metals.

Benefits of technology

Real-time monitoring of crevice corrosion and detailed testing of electrochemical parameters are realized, the mechanism of crevice corrosion is revealed, and the crevice corrosion performance between different metal materials can be evaluated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003106928880000011
    Figure HDA0003106928880000011
  • Figure HDA0003106928880000021
    Figure HDA0003106928880000021
  • Figure HDA0003106928880000031
    Figure HDA0003106928880000031
Patent Text Reader

Abstract

The present invention relates to the field of corrosion electrochemical experiments, specifically to a crevice corrosion electrochemical testing device and its application, which are used to monitor electrochemical signals in the crevice corrosion process. In the device, a crevice sample is embedded in a lower polytetrafluoroethylene (PTFE) mold, and a glass tube with a porous ceramic plug and a counter electrode are embedded in an upper PTFE mold. The porous ceramic plug is only conductive and does not exchange solutions. During the experiment, the glass tube is filled with an experimental solution, and then a reference electrode is inserted into the glass tube; a PTFE gasket is placed between the upper and lower molds, and the upper and lower molds are tightened with PTFE bolts to construct a crevice, so that a three-electrode two-loop system is realized in the crevice, and a three-electrode two-loop system is also set outside the crevice. The present invention can monitor the crevice current and coupling potential, and can also test the electrochemical signals of samples inside and outside the crevice, and can also be used to monitor the electrochemical signals during crevice corrosion between dissimilar materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of corrosion electrochemical experiments, in particular to a crevice corrosion electrochemical testing device and application thereof. Background Art

[0002] Many equipment and metal components will cause narrow gaps due to unreasonable design or processing, such as flange connection surfaces, nut tightening surfaces, gaps between heat transfer tubes and support plates of nuclear power steam generators, etc., and many gaps are formed between dissimilar metals. The corrosive medium in the gap is in a stagnant state, which can easily cause local corrosion of metal materials in the gap. This local corrosion behavior is generally called crevice corrosion. When crevice corrosion occurs, the consumption rate of oxygen in the gap is much greater than the diffusion rate of external oxygen into the gap, resulting in oxygen deficiency in the gap. The cathode oxygen absorption reaction relies on the outside of the gap, and the anodic dissolution of the metal continues to occur inside the gap, forming an oxygen concentration cell. The diffusion of metal cations dissolved in the gap is restricted, and the metal cations are hydrolyzed in the gap to reduce the pH of the crevice solution. At the same time, due to the principle of electrical neutrality, Cl - It will migrate into the gap and concentrate in the gap, eventually increasing the corrosion and dissolution rate of the metal in the gap. Crevice corrosion is hidden, has a long incubation period, has no obvious signs, and is difficult to detect. Once it starts, its rate will increase rapidly and cause serious damage to the material.

[0003] The evaluation method of crevice corrosion resistance of metal materials is currently mainly based on ASTM G48 and GB / T 10127 standards. The current standards have many defects: first, the methods specified in these two standards are carried out under specific conditions and cannot reflect the crevice corrosion resistance of materials under actual working conditions; second, they cannot reflect the process and mechanism of crevice corrosion; finally, the crevice width is uncontrollable and the crevice corrosion resistance of materials under different crevice conditions cannot be evaluated. Although the experimental device disclosed in the patent document (CN103528944 A) can monitor the electrochemical signals during crevice corrosion in real time, it cannot monitor the electrochemical signals of samples in the crevice. In addition, the above-mentioned several disclosed standards or devices cannot evaluate the crevice corrosion performance between dissimilar metal materials. Summary of the invention

[0004] The purpose of the present invention is to provide a crevice corrosion electrochemical testing device and its application. The experimental device can monitor the electrochemical signals during crevice corrosion under different crevice widths, and can also test the electrochemical parameters of samples inside and outside the crevice respectively. It can also monitor the electrochemical signals during crevice corrosion between dissimilar metal materials and evaluate the crevice corrosion performance between dissimilar metal materials.

[0005] The technical solution of the present invention is:

[0006] A crevice corrosion electrochemical testing device, comprising: a sample outside the crevice, a reference electrode outside the crevice, a counter electrode outside the crevice, a sample inside the crevice, a reference electrode inside the crevice, a counter electrode inside the crevice, a solution pool, a glass tube with a porous ceramic plug at the first bottom end, the porous ceramic plug, a first epoxy resin tank, a lower PTFE mold, an upper PTFE mold, a PTFE gasket, a PTFE bolt, a glass tube with a porous ceramic plug at the second bottom end, and a second epoxy resin tank. The specific structure is as follows:

[0007] An out-of-gap sample, an out-of-gap counter electrode, an in-gap sample, and an in-gap counter electrode are arranged in the solution in the solution pool; the out-of-gap sample is embedded in the groove on the side of the first epoxy resin tank as an out-of-gap working electrode; an out-of-gap reference electrode and an out-of-gap counter electrode are arranged on one side of the outer surface of the out-of-gap sample; a glass tube with a porous ceramic plug at the first bottom end is vertically inserted into the solution pool; a porous ceramic plug is installed at the bottom of the glass tube with a porous ceramic plug at the first bottom end; and the lower end of the out-of-gap reference electrode is inserted into the solution in the glass tube with a porous ceramic plug at the first bottom end;

[0008] The lower PTFE mold, PTFE gasket and upper PTFE mold are arranged in sequence from bottom to top and connected by PTFE bolts to form a gap at the PTFE gasket. The sample in the gap is embedded in the groove above the second epoxy resin groove as the working electrode in the gap. The second epoxy resin groove is arranged in the lower PTFE mold. The upper surface of the sample in the gap is located on the upper surface of the lower PTFE mold and corresponds to the gap; the counter electrode in the gap is embedded in the lower surface of the upper PTFE mold and corresponds to the gap; the glass tube with a porous ceramic plug at the second bottom end is vertically inserted into the upper PTFE mold, and a porous ceramic plug is installed at the bottom of the glass tube with a porous ceramic plug at the second bottom end, and the lower surface of the porous ceramic plug is located on the lower surface of the upper PTFE mold and corresponds to the gap. The lower end of the reference electrode in the gap is inserted in the solution in the glass tube with a porous ceramic plug at the second bottom end.

[0009] In the crevice corrosion electrochemical testing device, an air inlet pipe is installed on one side of the top of the solution pool, and the lower end of the air inlet pipe extends to the bottom of the solution pool. An air outlet pipe is installed on the other side of the top of the solution pool, and the air outlet pipe is located above the solution in the solution pool.

[0010] The crevice corrosion electrochemical testing device has a groove at one end of the PTFE gasket to form a concave sheet structure, and holes for PTFE bolts to pass through are respectively provided at the four corners of the structure.

[0011] The application of the crevice corrosion electrochemical testing device comprises the following steps:

[0012] (1) Use the second epoxy resin tank to embed the sample in the gap into the lower PTFE mold, exposing 1 cm 2The working area of ​​the second bottom end of the glass tube with a porous ceramic plug is inserted into the upper PTFE mold, the counter electrode in the gap is embedded in the upper PTFE mold, and the sample outside the gap is embedded with the first epoxy resin groove, exposing 1cm 2 working area;

[0013] (2) processing the PTFE gasket into a designed thickness and placing the PTFE gasket between the lower PTFE mold and the upper PTFE mold;

[0014] (3) Using PTFE bolts to tighten the lower PTFE mold, the PTFE gasket, and the upper PTFE mold to construct a gap, wherein the gap is located in the grooved area of ​​the PTFE gasket, and the gap width is controlled by the thickness of the PTFE gasket. The gap width is controlled by changing the thickness of the PTFE gasket;

[0015] (4) filling the glass tube with a porous ceramic plug at the second bottom end with the experimental solution, and conducting electricity through the porous ceramic plug;

[0016] (5) placing the reference electrode inside the gap in the glass tube with a porous ceramic plug at the second bottom end filled with the experimental solution, forming a three-electrode two-circuit system inside the gap with the counter electrode inside the gap and the sample inside the gap; placing the glass tube with a porous ceramic plug at the first bottom end outside the gap, placing the reference electrode outside the gap in the glass tube with a porous ceramic plug at the first bottom end filled with the experimental solution, forming a three-electrode system outside the gap with the counter electrode outside the gap and the sample outside the gap;

[0017] (6) During the experiment, the three-electrode system inside and outside the crevice is placed in a solution pool, and all electrodes are connected to the electrochemical workstation through electrode leads. The crevice current and coupling potential during crevice corrosion are monitored by a zero resistance ammeter, or the electrochemical parameters of the samples inside and outside the crevice are tested separately.

[0018] A crevice corrosion electrochemical testing device, comprising: a sample outside the crevice, a reference electrode outside the crevice, a solution pool, a glass tube with a porous ceramic plug at the first bottom end, the porous ceramic plug, a first epoxy resin tank, a lower PTFE mold, an upper PTFE mold, a PTFE gasket, a PTFE bolt, a second epoxy resin tank, a sample inside the crevice made of a different material from the sample outside the crevice, and a sample inside the crevice made of the same material as the sample outside the crevice. The specific structure is as follows:

[0019] An out-of-gap sample, an in-gap sample made of a different material from the out-of-gap sample, and an in-gap sample made of the same material as the out-of-gap sample are arranged in the solution in the solution pool; the out-of-gap sample is embedded in a groove on the side of the first epoxy resin tank as an out-of-gap working electrode; an out-of-gap reference electrode is arranged on one side of the outer surface of the out-of-gap sample; a glass tube with a porous ceramic plug at the first bottom end is vertically inserted into the solution pool; a porous ceramic plug is installed at the bottom of the glass tube with a porous ceramic plug at the first bottom end; and the lower end of the out-of-gap reference electrode is inserted into the solution in the glass tube with a porous ceramic plug at the first bottom end;

[0020] The lower PTFE mold, the PTFE gasket and the upper PTFE mold are arranged in sequence from bottom to top and connected by PTFE bolts to form a gap at the PTFE gasket; the sample inside the gap, which is made of the same material as the sample outside the gap, is embedded in the groove above the second epoxy resin groove as the working electrode inside the gap, the second epoxy resin groove is arranged in the lower PTFE mold, and the upper surface of the sample inside the gap, which is made of the same material as the sample outside the gap, is located on the upper surface of the lower PTFE mold and corresponds to the gap; the sample inside the gap, which is made of a different material from the sample outside the gap, is embedded in the groove below the third epoxy resin groove as the working electrode inside the gap, the third epoxy resin groove is arranged in the upper PTFE mold, and the lower surface of the sample inside the gap, which is made of a different material from the sample outside the gap, is located on the lower surface of the upper PTFE mold and corresponds to the gap.

[0021] In the crevice corrosion electrochemical testing device, an air inlet pipe is installed on one side of the top of the solution pool, and the lower end of the air inlet pipe extends to the bottom of the solution pool. An air outlet pipe is installed on the other side of the top of the solution pool, and the air outlet pipe is located above the solution in the solution pool.

[0022] The crevice corrosion electrochemical testing device has a groove at one end of the PTFE gasket to form a concave sheet structure, and holes for PTFE bolts to pass through are respectively provided at the four corners of the structure.

[0023] The application of the crevice corrosion electrochemical testing device comprises the following steps:

[0024] (1) The second epoxy resin groove is used to embed the sample inside the gap, which is made of the same material as the sample outside the gap, in the lower PTFE mold. The third epoxy resin groove is used to embed the sample inside the gap, which is made of the same material as the sample outside the gap, in the upper PTFE mold. The sample outside the gap is embedded in the first epoxy resin groove. All samples are exposed for 1 cm. 2 working area;

[0025] (2) processing the PTFE gasket into a designed thickness and placing the PTFE gasket between the lower PTFE mold and the upper PTFE mold;

[0026] (3) Using PTFE bolts to tighten the lower PTFE mold, the PTFE gasket, and the upper PTFE mold to construct a gap, wherein the gap is located in the grooved area of ​​the PTFE gasket, and the gap width is controlled by the thickness of the PTFE gasket. The gap width is controlled by changing the thickness of the PTFE gasket;

[0027] (4) placing the sample outside the gap and the glass tube with a porous ceramic plug at the first bottom end outside the gap, and placing the reference electrode outside the gap into the glass tube with a porous ceramic plug at the first bottom end filled with the experimental solution;

[0028] (5) During the experiment, the electrodes inside and outside the gap are placed in a solution pool, and all electrodes are connected to an electrochemical workstation through electrode leads. A multi-channel zero-resistance ammeter is used to monitor the coupling current and coupling potential of the three samples inside and outside the gap, or a single-channel zero-resistance ammeter is used to intermittently measure the coupling current and coupling potential of the three samples inside and outside the gap.

[0029] The application of the crevice corrosion electrochemical test device uses a single-channel zero-resistance ammeter to intermittently measure the coupling current and coupling potential of three samples inside and outside the crevice. The process is as follows:

[0030] When measuring the coupling current reflecting the corrosion state of the sample, sample two and sample three are connected and coupled by a wire, and then the coupling current between sample one and the coupled sample two and sample three is measured by a zero-resistance ammeter; when measuring the coupling current reflecting the corrosion state of sample two, sample one and sample three are connected and coupled by a wire, and then the coupling current between sample two and the coupled sample one and sample three is measured by a zero-resistance ammeter; when measuring the coupling current reflecting the corrosion state of sample three, sample one and sample two are connected and coupled by a wire, and then the coupling current between sample three and the coupled sample one and sample two is measured by a zero-resistance ammeter.

[0031] The advantages and beneficial effects of the present invention are:

[0032] 1. The present invention provides a crevice corrosion electrochemical testing device. By separating the anode and cathode, a three-electrode two-circuit system is designed inside and outside the crevice respectively. It can not only monitor the electrochemical signal during crevice corrosion, but also test the electrochemical parameters of samples inside and outside the crevice respectively, which is conducive to revealing the crevice corrosion mechanism.

[0033] 2. The present invention ingeniously utilizes the function of porous ceramic plugs that only conduct electricity but do not exchange solutions. A glass tube with a porous ceramic plug at the bottom is embedded in the upper mold. During the experiment, a reference electrode is inserted into the glass tube filled with the experimental solution, and the reference electrode is successfully introduced into the gap.

[0034] 3. The present invention controls the width of the gap by changing the thickness of the polytetrafluoroethylene (PTFE) gasket, and controls the depth of the gap by changing the size of the PTFE mold.

[0035] 4. The present invention designs an experimental device for monitoring the electrochemical signals of crevice corrosion between dissimilar metals, and adopts a multi-channel zero resistance ammeter (ZRA) to monitor in real time or a single-channel ZRA to monitor intermittently the electrochemical signals of crevice corrosion between dissimilar metals, which is helpful to reveal the crevice corrosion mechanism between dissimilar metals.

[0036] 5. The present invention has a simple structure, is easy to install and disassemble, and is convenient to operate. The PTFE mold and gasket are reusable and have low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of crevice corrosion electrochemical test device. In the figure, 1-sample outside the crevice, 2-reference electrode outside the crevice, 3-counter electrode outside the crevice, 4-sample inside the crevice, 5-reference electrode inside the crevice, 6-counter electrode inside the crevice, 7-solution pool, 8-glass tube with porous ceramic plug at the first bottom end, 9-porous ceramic plug, 10-first epoxy resin tank, 11-lower PTFE mold, 12-upper PTFE mold, 13-PTFE gasket, 14-PTFE bolt, 15-glass tube with porous ceramic plug at the second bottom end, 16-second epoxy resin tank, 17-inlet pipe, 18-outlet pipe.

[0038] Figure 2 Schematic diagram of PTFE gasket.

[0039] Figure 3 Schematic diagram of the electrochemical test device for crevice corrosion between dissimilar metal materials. In the figure, 1-sample outside the crevice, 2-reference electrode outside the crevice, 7-solution pool, 8-glass tube with a porous ceramic plug at the first bottom, 9-porous ceramic plug, 10-first epoxy resin tank, 11-lower PTFE mold, 12-upper PTFE mold, 13-PTFE gasket, 14-PTFE bolt, 16-second epoxy resin tank, 17-inlet pipe, 18-outlet pipe, 19-sample inside the crevice of different material from the sample outside the crevice, 20-sample inside the crevice of the same material as the sample outside the crevice, 21-third epoxy resin tank.

[0040] Figure 4 Schematic diagram of the method of intermittently monitoring the coupled current of crevice corrosion between dissimilar metals using a single-channel ZRA. In the figure, 1 and 2 are samples of the same material, and 2 and 3 are samples of dissimilar materials. Figure 4 (a)- Figure 4 (c) Schematic diagram of the coupled current method for monitoring the corrosion status of samples 1-3.

[0041] Figure 5 To adopt Figure 1The crevice corrosion electrochemical testing device shown in the figure shows the results of crevice corrosion electrochemical testing of 690 nickel-based alloy in a 3.5wt% NaCl aqueous solution at 70°C. Figure 5 (a) is the gap current and coupling potential monitored by ZRA, the horizontal axis Time represents time (h), the left vertical axis Galvanic current represents coupling current (μA), and the right vertical axis Galvanic potential represents coupling potential (V); Figure 5 (b) The electrochemical impedance spectroscopy test results of the samples inside and outside the gap, the horizontal axis Z′ represents the real part of the impedance (kΩcm 2 ), the ordinate -Z″ represents the imaginary part of impedance (kΩcm 2 ); Figure 5 In (b), 1 – sample outside the gap, 2 – sample inside the gap.

[0042] Figure 6 To adopt Figure 3 The electrochemical test device for crevice corrosion between dissimilar metal materials shown in the figure shows the results of crevice corrosion electrochemical test between dissimilar metal materials 690 nickel-based alloy and 405 stainless steel in a 3.5wt% NaCl aqueous solution at 70°C. The sample outside the crevice is 690 nickel-based alloy, and the two samples inside the crevice are 690 nickel-based alloy and 405 stainless steel, respectively. Intermittent measurement is performed using a single-channel ZRA. The horizontal axis Time represents time (h), the left vertical axis Galvanic current represents coupling current (μA), and the right vertical axis Galvanic potential represents coupling potential (V). In the figure, 1-coupled current reflecting the corrosion state of 690 nickel-based alloy outside the crevice, 2-coupled current reflecting the corrosion state of 690 nickel-based alloy inside the crevice, 3-coupled current reflecting the corrosion state of 405 stainless steel inside the crevice, and 4-coupled potentials of the three samples. DETAILED DESCRIPTION

[0043] like Figure 1 As shown, the present invention provides a crevice corrosion electrochemical testing device, which mainly includes: a sample outside the crevice 1, a reference electrode outside the crevice 2, a counter electrode outside the crevice 3, a sample inside the crevice 4, a reference electrode inside the crevice 5, a counter electrode inside the crevice 6, a solution pool 7, a glass tube 8 with a porous ceramic plug at the first bottom end, a porous ceramic plug 9, a first epoxy resin groove 10, a lower PTFE mold 11, an upper PTFE mold 12, a PTFE gasket 13, a PTFE bolt 14, a glass tube 15 with a porous ceramic plug at the second bottom end, a second epoxy resin groove 16, an air inlet pipe 17, and an air outlet pipe 18. The specific structure is as follows:

[0044] An outside-gap sample 1 (working electrode outside the gap), an outside-gap counter electrode 3, an inside-gap sample 4 (working electrode inside the gap), and an inside-gap counter electrode 6 are arranged in the solution in the solution pool 7. An air inlet pipe 17 is installed on one side of the top of the solution pool 7, and the lower end of the air inlet pipe 17 extends to the bottom of the solution pool 7. An air outlet pipe 18 is installed on the other side of the top of the solution pool 7, and the air outlet pipe 18 is located above the solution in the solution pool 7.

[0045] The out-of-gap sample 1 is embedded in the side groove of the first epoxy resin groove 10 as the out-of-gap working electrode, and the out-of-gap reference electrode 2 and the out-of-gap counter electrode 3 are arranged on one side of the outer surface of the out-of-gap sample 1. The glass tube 8 with a porous ceramic plug at the first bottom end is vertically inserted into the solution pool 7, and the porous ceramic plug 9 is installed at the bottom of the glass tube 8 with a porous ceramic plug at the first bottom end. The lower end of the out-of-gap reference electrode 2 is inserted in the solution in the glass tube 8 with a porous ceramic plug at the first bottom end.

[0046] The lower PTFE mold 11, the PTFE gasket 13, and the upper PTFE mold 12 are arranged in sequence from bottom to top and connected by PTFE bolts 14, a gap is formed at the PTFE gasket 13, and the sample 4 in the gap is embedded in the groove above the second epoxy resin groove 16 as the working electrode in the gap. The second epoxy resin groove 16 is arranged in the lower PTFE mold 11, and the upper surface of the sample 4 in the gap is located on the upper surface of the lower PTFE mold 11 and corresponds to the gap; the gap The inner counter electrode 6 is embedded in the lower surface of the upper PTFE mold 12 and corresponds to the gap; the glass tube 15 with a porous ceramic plug at the second bottom end is vertically inserted into the upper PTFE mold 12, and the porous ceramic plug is installed at the bottom of the second glass tube 15 with a porous ceramic plug at the bottom, and the lower surface of the porous ceramic plug is located on the lower surface of the upper PTFE mold 12 and corresponds to the gap, and the lower end of the reference electrode 5 in the gap is inserted in the solution in the second glass tube 15 with a porous ceramic plug at the bottom end.

[0047] In the specific implementation process, the operation steps are as follows:

[0048] (1) The sample 4 in the gap is embedded in the lower PTFE mold 11 using the second epoxy resin tank 16, with only 1 cm exposed. 2 The second bottom end of the glass tube with a porous ceramic plug 15 is inserted into the upper PTFE mold 12, the gap electrode 6 is embedded in the upper PTFE mold 12, the gap outside the sample 1 is also embedded with the first epoxy resin groove 10, only 1cm exposed 2 working area.

[0049] (2) Figure 2As shown, the PTFE gasket 13 is processed into the designed thickness, a groove is cut at one end of the PTFE gasket 13 to form a concave sheet structure, and holes for the PTFE bolts 14 to pass through are respectively opened at the four corners of the structure, and the PTFE gasket 13 is placed between the lower PTFE mold 11 and the upper PTFE mold 12.

[0050] (3) The lower PTFE mold 11, the PTFE gasket 13, and the upper PTFE mold 12 are tightened with a PTFE bolt 14 to construct a gap. The gap is located in the grooved area of ​​the PTFE gasket 13. The gap width is controlled by the thickness of the PTFE gasket 13. The gap width is controlled by changing the thickness of the PTFE gasket 13.

[0051] (4) The experimental solution is filled in the glass tube 15 with a porous ceramic plug at the second bottom. The porous ceramic plug only conducts electricity without exchanging solutions. Therefore, the solution in the glass tube 15 with a porous ceramic plug at the second bottom will not affect the gap solution.

[0052] (5) The reference electrode 5 inside the gap is placed in a glass tube 15 with a second bottom end having a porous ceramic plug filled with the experimental solution, and together with the counter electrode 6 inside the gap and the sample 4 inside the gap, a three-electrode two-circuit system is formed inside the gap; a glass tube 8 with a first bottom end having a porous ceramic plug is placed outside the gap, and the reference electrode 2 outside the gap is placed in the glass tube 8 with a first bottom end having a porous ceramic plug filled with the experimental solution, and together with the counter electrode 3 outside the gap and the sample 1 outside the gap, a three-electrode system is formed outside the gap.

[0053] (6) During the experiment, the three-electrode system inside and outside the crevice is placed in the solution pool 7, and all electrodes are connected to the electrochemical workstation through electrode leads. The crevice current and coupling potential during crevice corrosion can be monitored by ZRA, and the electrochemical parameters (including electrode potential, polarization curve, and electrochemical impedance spectrum) of the samples inside and outside the crevice can be tested respectively.

[0054] like Figure 3 As shown, the present invention provides an electrochemical test device for crevice corrosion between dissimilar metal materials, which mainly includes: a sample outside the crevice 1, a reference electrode outside the crevice 2, a solution pool 7, a glass tube 8 with a porous ceramic plug at the first bottom end, a porous ceramic plug 9, a first epoxy resin tank 10, a lower PTFE mold 11, an upper PTFE mold 12, a PTFE gasket 13, a PTFE bolt 14, a second epoxy resin tank 16, an air inlet pipe 17, an air outlet pipe 18, a sample inside the crevice 19 of a different material from the sample outside the crevice, and a sample inside the crevice 20 of the same material as the sample outside the crevice. The specific structure is as follows:

[0055] An outside-gap sample 1 (working electrode outside the gap), an inside-gap sample 19 (working electrode inside the gap) made of a different material from the outside-gap sample, and an inside-gap sample 20 (working electrode inside the gap) made of the same material as the outside-gap sample are arranged in the solution in the solution pool 7. An air inlet pipe 17 is installed on one side of the top of the solution pool 7, and the lower end of the air inlet pipe 17 extends to the bottom of the solution pool 7. An air outlet pipe 18 is installed on the other side of the top of the solution pool 7, and the air outlet pipe 18 is located above the solution in the solution pool 7.

[0056] The out-of-gap sample 1 is embedded in the side groove of the first epoxy resin groove 10 as the out-of-gap working electrode, and the out-of-gap reference electrode 2 is arranged on one side of the outer surface of the out-of-gap sample 1. The glass tube 8 with a porous ceramic plug at the first bottom end is vertically inserted into the solution pool 7, and the porous ceramic plug 9 is installed at the bottom of the glass tube 8 with a porous ceramic plug at the first bottom end. The lower end of the out-of-gap reference electrode 2 is inserted into the solution in the glass tube 8 with a porous ceramic plug at the first bottom end.

[0057] The lower PTFE mold 11, the PTFE gasket 13, and the upper PTFE mold 12 are arranged in sequence from bottom to top and connected by PTFE bolts 14 to form a gap at the PTFE gasket 13; the sample 20 in the gap, which is made of the same material as the sample outside the gap, is embedded in the groove above the second epoxy resin groove 16 as the working electrode in the gap. The second epoxy resin groove 16 is arranged in the lower PTFE mold 11, and the upper surface of the sample 20 in the gap, which is made of the same material as the sample outside the gap, is located on the upper surface of the lower PTFE mold 11 and corresponds to the gap; the sample 19 in the gap, which is made of a different material from the sample outside the gap, is embedded in the groove below the third epoxy resin groove 21 as the working electrode in the gap. The third epoxy resin groove 21 is arranged in the upper PTFE mold 12, and the lower surface of the sample 19 in the gap, which is made of a different material from the sample outside the gap, is located on the lower surface of the upper PTFE mold 12 and corresponds to the gap.

[0058] In the specific implementation process, the operation steps are as follows:

[0059] (1) The in-slit sample 20 made of the same material as the sample outside the gap is embedded in the lower PTFE mold 11 using the second epoxy resin groove 16, the in-slit sample 20 made of the same material as the sample outside the gap is embedded in the upper PTFE mold 12 using the third epoxy resin groove 21, and the sample outside the gap 1 is embedded in the first epoxy resin groove 10. All samples are exposed for 1 cm 2 working area.

[0060] (2) Figure 2 As shown, the PTFE gasket 13 is processed into the designed thickness, and a groove is cut at one end of the PTFE gasket 13 to form a concave sheet structure, and holes for the PTFE bolts 14 to pass through are respectively opened at the four corners; the PTFE gasket 13 is placed between the lower PTFE mold 11 and the upper PTFE mold 12.

[0061] (3) The lower PTFE mold 11, the PTFE gasket 13, and the upper PTFE mold 12 are tightened with a PTFE bolt 14 to construct a gap. The gap is located in the grooved area of ​​the PTFE gasket 13. The gap width is controlled by the thickness of the PTFE gasket 13. The gap width is controlled by changing the thickness of the PTFE gasket 13.

[0062] (4) Place the sample 1 outside the gap and the glass tube 8 with a porous ceramic plug at the first bottom end outside the gap, and place the reference electrode 2 outside the gap into the glass tube 8 with a porous ceramic plug at the first bottom end filled with the experimental solution.

[0063] (5) During the experiment, the electrodes inside and outside the gap are placed in the solution pool 7, and all the electrodes are connected to the electrochemical workstation through electrode leads. A multi-channel ZRA is used to monitor the coupling current and coupling potential of the three samples inside and outside the gap, or a single-channel ZRA is used to intermittently measure the coupling current and coupling potential of the three samples inside and outside the gap.

[0064] (6) When using a single-channel ZRA to intermittently measure the coupling current and coupling potential of three samples inside and outside the gap, use Figure 4 The test method shown. When measuring the coupling current reflecting the corrosion state of sample 1, sample 2 and sample 3 are connected and coupled with a wire, and then the coupling current between sample 1 and the coupled sample 2 and sample 3 is measured with a ZRA; when measuring the coupling current reflecting the corrosion state of sample 2, sample 1 and sample 3 are connected and coupled with a wire, and then the coupling current between sample 2 and the coupled sample 1 and sample 3 is measured with a ZRA; when measuring the coupling current reflecting the corrosion state of sample 3, sample 1 and sample 2 are connected and coupled with a wire, and then the coupling current between sample 3 and the coupled sample 1 and sample 2 is measured with a ZRA.

[0065] Below, the present invention is further described in detail by examples.

[0066] Embodiment 1:

[0067] In the embodiment, the Figure 1 The crevice corrosion electrochemical test device shown in the figure is used to conduct crevice corrosion electrochemical test on 690 nickel-based alloy in 70℃ 3.5wt% NaCl aqueous solution. The thickness of the PTFE gasket is 0.2mm, that is, the controlled crevice width is 0.2mm; the samples inside and outside the crevice are all 690 nickel-based alloy. First, the crevice current and coupling potential during crevice corrosion are monitored by ZRA for 24 hours, as shown in Figure 2. Figure 5 As shown in (a), the crevice current is about 1μA, indicating that crevice corrosion has indeed occurred. Then, the electrochemical impedance spectroscopy of the samples inside and outside the crevice was tested using a three-electrode system inside and outside the crevice. The test results are shown in Figure 5(b) shows the Nyquist Figure 5 (b) The arc radius of -2 is obviously smaller than that of the sample outside the gap Figure 5 (b)-1, indicating that the corrosion of the sample inside the crevice is more serious than that of the sample outside the crevice. The above examples prove that the crevice corrosion electrochemical test device is reliable, which can monitor the crevice current and coupling potential during crevice corrosion and test the electrochemical parameters of the samples inside and outside the crevice respectively.

[0068] Embodiment 2:

[0069] In the embodiment, the Figure 3 The electrochemical test device for crevice corrosion between dissimilar metal materials shown in the figure is used to conduct crevice corrosion electrochemical test between 690 nickel-based alloy and 405 stainless steel dissimilar metal materials in a 70°C 3.5wt% NaCl aqueous solution. The sample outside the crevice is 690 nickel-based alloy, and the two samples inside the crevice are 690 nickel-based alloy and 405 stainless steel, respectively. Single-channel ZRA is used according to Figure 4 The measurement method shown performs intermittent measurements. Figure 6 The figure shows the test results: 1-coupling current reflecting the corrosion state of 690 nickel-based alloy outside the gap, 2-coupling current reflecting the corrosion state of 690 nickel-based alloy inside the gap, 3-coupling current reflecting the corrosion state of 405 stainless steel inside the gap, and 4-coupling potential of the three samples. The coupling current of 690 nickel-based alloy outside the gap is always negative, indicating that it is always the cathode; the coupling current of 405 stainless steel inside the gap is always positive, indicating that it is always the anode; the coupling current of 690 nickel-based alloy inside the gap is positive in the first 4 hours and negative after 4 hours, indicating that it is the anode in the first 4 hours and the cathode after 4 hours. The above embodiments prove that the electrochemical test device for crevice corrosion between dissimilar metal materials is reliable and can monitor the coupling current and coupling potential during crevice corrosion between dissimilar metals.

[0070] The results of the embodiments show that the present invention can monitor the crevice current and coupling potential, test the electrochemical signals of samples inside and outside the crevice, and can also be used to monitor the electrochemical signals of crevice corrosion between dissimilar materials.

Claims

1. A crevice corrosion electrochemical testing device, characterized in that: The device comprises: a sample outside the gap, a reference electrode outside the gap, a counter electrode outside the gap, a sample inside the gap, a reference electrode inside the gap, a counter electrode inside the gap, a solution pool, a glass tube with a porous ceramic plug at the first bottom end, the porous ceramic plug, a first epoxy resin tank, a lower PTFE mold, an upper PTFE mold, a PTFE gasket, a PTFE bolt, a glass tube with a porous ceramic plug at the second bottom end, and a second epoxy resin tank. The specific structure is as follows: An out-of-gap sample, an out-of-gap counter electrode, an in-gap sample, and an in-gap counter electrode are arranged in the solution in the solution pool; the out-of-gap sample is embedded in the groove on the side of the first epoxy resin tank as an out-of-gap working electrode; an out-of-gap reference electrode and an out-of-gap counter electrode are arranged on one side of the outer surface of the out-of-gap sample; a glass tube with a porous ceramic plug at the first bottom end is vertically inserted into the solution pool; a porous ceramic plug is installed at the bottom of the glass tube with a porous ceramic plug at the first bottom end; and the lower end of the out-of-gap reference electrode is inserted into the solution in the glass tube with a porous ceramic plug at the first bottom end; The lower PTFE mold, the PTFE gasket, and the upper PTFE mold are arranged in sequence from bottom to top and connected by PTFE bolts, a gap is formed at the PTFE gasket, and the sample in the gap is embedded in the groove above the second epoxy resin groove as the working electrode in the gap, the second epoxy resin groove is arranged in the lower PTFE mold, and the upper surface of the sample in the gap is located on the upper surface of the lower PTFE mold and corresponds to the gap; the counter electrode in the gap is embedded in the lower surface of the upper PTFE mold and corresponds to the gap; the glass tube with a porous ceramic plug at the second bottom end is vertically inserted into the upper PTFE mold, and a porous ceramic plug is installed at the bottom of the glass tube with a porous ceramic plug at the second bottom end, and the lower surface of the porous ceramic plug is located on the lower surface of the upper PTFE mold and corresponds to the gap, and the lower end of the reference electrode in the gap is inserted in the solution in the glass tube with a porous ceramic plug at the second bottom end; Filling the experimental solution in the glass tube with a porous ceramic plug at the second bottom end, wherein the porous ceramic plug is a porous ceramic plug that only conducts electricity but does not exchange the solution; A groove is formed at one end of the PTFE gasket to form a concave sheet structure, and holes for PTFE bolts to pass through are respectively formed at the four corners of the structure.

2. The crevice corrosion electrochemical testing device according to claim 1, characterized in that: An air inlet pipe is installed on one side of the top of the solution pool, and the lower end of the air inlet pipe extends to the bottom of the solution pool. An air outlet pipe is installed on the other side of the top of the solution pool, and the air outlet pipe is located above the solution in the solution pool.

3. An application of the crevice corrosion electrochemical testing device according to any one of claims 1 to 2, characterized in that: The steps include: (1) Use the second epoxy resin groove to embed the sample in the gap into the lower PTFE mold, exposing 1 cm 2 The working area of ​​the second glass tube with a porous ceramic plug at the bottom is inserted into the upper PTFE mold, the counter electrode in the gap is embedded in the upper PTFE mold, and the sample outside the gap is embedded with the first epoxy resin groove, exposing 1 cm 2 working area; (2) Processing the PTFE gasket to the designed thickness and placing the PTFE gasket between the lower PTFE mold and the upper PTFE mold; (3) Using PTFE bolts to tighten the lower PTFE mold, the PTFE gasket, and the upper PTFE mold to construct a gap. The gap is located in the grooved area of ​​the PTFE gasket. The gap width is controlled by the thickness of the PTFE gasket. The gap width is controlled by changing the thickness of the PTFE gasket. (4) filling the glass tube with a porous ceramic plug at the second bottom with the experimental solution, and conducting electricity through the porous ceramic plug; (5) placing the reference electrode inside the gap in the second glass tube with a porous ceramic plug at the bottom filled with the experimental solution, forming a three-electrode two-circuit system inside the gap with the counter electrode inside the gap and the sample inside the gap; placing the glass tube with a porous ceramic plug at the first bottom outside the gap, placing the reference electrode outside the gap in the first glass tube with a porous ceramic plug at the bottom filled with the experimental solution, forming a three-electrode system outside the gap with the counter electrode outside the gap and the sample outside the gap; (6) During the experiment, the three-electrode system inside and outside the crevice is placed in a solution pool, and all electrodes are connected to the electrochemical workstation through electrode leads. The crevice current and coupling potential during crevice corrosion are monitored by a zero resistance ammeter, or the electrochemical parameters of the samples inside and outside the crevice are tested separately.

4. A crevice corrosion electrochemical testing device, characterized in that: The device comprises: a sample outside the gap, a reference electrode outside the gap, a solution pool, a glass tube with a porous ceramic plug at the first bottom, a porous ceramic plug, a first epoxy resin tank, a lower PTFE mold, an upper PTFE mold, a PTFE gasket, a PTFE bolt, a second epoxy resin tank, a sample inside the gap that is made of a different material from the sample outside the gap, and a sample inside the gap that is made of the same material as the sample outside the gap. The specific structure is as follows: An out-of-gap sample, an in-gap sample made of a different material from the out-of-gap sample, and an in-gap sample made of the same material as the out-of-gap sample are arranged in the solution in the solution pool; the out-of-gap sample is embedded in a groove on the side of the first epoxy resin tank as an out-of-gap working electrode; an out-of-gap reference electrode is arranged on one side of the outer surface of the out-of-gap sample; a glass tube with a porous ceramic plug at the first bottom end is vertically inserted into the solution pool; a porous ceramic plug is installed at the bottom of the glass tube with a porous ceramic plug at the first bottom end; and the lower end of the out-of-gap reference electrode is inserted into the solution in the glass tube with a porous ceramic plug at the first bottom end; The lower PTFE mold, the PTFE gasket, and the upper PTFE mold are arranged in sequence from bottom to top and connected by PTFE bolts to form a gap at the PTFE gasket; the sample inside the gap, which is made of the same material as the sample outside the gap, is embedded in the upper groove of the second epoxy resin groove as the working electrode inside the gap, the second epoxy resin groove is arranged in the lower PTFE mold, and the upper surface of the sample inside the gap, which is made of the same material as the sample outside the gap, is located on the upper surface of the lower PTFE mold and corresponds to the gap; the sample inside the gap, which is made of a different material from the sample outside the gap, is embedded in the lower groove of the third epoxy resin groove as the working electrode inside the gap, the third epoxy resin groove is arranged in the upper PTFE mold, and the lower surface of the sample inside the gap, which is made of a different material from the sample outside the gap, is located on the lower surface of the upper PTFE mold and corresponds to the gap; Filling the glass tube with a porous ceramic plug at the first bottom with an experimental solution, wherein the porous ceramic plug is a porous ceramic plug that only conducts electricity but does not exchange the solution; A groove is formed at one end of the PTFE gasket to form a concave sheet structure, and holes for PTFE bolts to pass through are respectively formed at the four corners of the structure.

5. The crevice corrosion electrochemical testing device according to claim 4, characterized in that: An air inlet pipe is installed on one side of the top of the solution pool, and the lower end of the air inlet pipe extends to the bottom of the solution pool. An air outlet pipe is installed on the other side of the top of the solution pool, and the air outlet pipe is located above the solution in the solution pool.

6. Use of the crevice corrosion electrochemical testing device according to any one of claims 4 to 5, characterized in that: The steps include: (1) The second epoxy resin groove is used to embed the sample inside the gap, which is made of the same material as the sample outside the gap, in the lower PTFE mold. The third epoxy resin groove is used to embed the sample inside the gap, which is made of the same material as the sample outside the gap, in the upper PTFE mold. The sample outside the gap is embedded in the first epoxy resin groove. All samples are exposed for 1 cm. 2 working area; (2) Processing the PTFE gasket to the designed thickness and placing the PTFE gasket between the lower PTFE mold and the upper PTFE mold; (3) Using PTFE bolts to tighten the lower PTFE mold, the PTFE gasket, and the upper PTFE mold to construct a gap. The gap is located in the grooved area of ​​the PTFE gasket. The gap width is controlled by the thickness of the PTFE gasket. The gap width is controlled by changing the thickness of the PTFE gasket. (4) placing the sample outside the gap and the glass tube with a porous ceramic plug at the first bottom end outside the gap, and placing the reference electrode outside the gap into the glass tube with a porous ceramic plug at the first bottom end filled with the experimental solution; (5) During the experiment, the electrodes inside and outside the gap are placed in a solution pool. All electrodes are connected to the electrochemical workstation through electrode leads. A multi-channel zero-resistance ammeter is used to monitor the coupling current and coupling potential of the three samples inside and outside the gap, or a single-channel zero-resistance ammeter is used to intermittently measure the coupling current and coupling potential of the three samples inside and outside the gap.

7. Use of the crevice corrosion electrochemical testing device according to claim 6, characterized in that: The process of intermittently measuring the coupling current and coupling potential of three samples inside and outside the gap using a single-channel zero-resistance ammeter is as follows: When measuring the coupling current reflecting the corrosion state of the sample, sample two and sample three are connected and coupled by a wire, and then the coupling current between sample one and the coupled sample two and sample three is measured by a zero-resistance ammeter; when measuring the coupling current reflecting the corrosion state of sample two, sample one and sample three are connected and coupled by a wire, and then the coupling current between sample two and the coupled sample one and sample three is measured by a zero-resistance ammeter; when measuring the coupling current reflecting the corrosion state of sample three, sample one and sample two are connected and coupled by a wire, and then the coupling current between sample three and the coupled sample one and sample two is measured by a zero-resistance ammeter.

Citation Information

Patent Citations

  • Electrochemical performance testing device for crevice corrosion

    CN103528944A

  • Testing device and method for rapidly evaluating titanium alloy crevice corrosion

    CN112697686A